2023
DOI: 10.1002/adsc.202300647
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of the De Mayo Reaction: Unveiling a Photochemical and Photocatalytic Masked [2+2] Methodology for Organic Synthesis

Abstract: In 1962, Paul J. de Mayo initially described the photochemical reaction involving 1,3‐diketones and double bonds, resulting in the formation of 1,5‐diketones. Since then, this reaction has been extensively utilized for the synthesis of a wide range of fascinating natural products. Over time, this synthetic methodology has been applied to various carbonyl systems, including locked enol‐tautomers of diketones, β‐keto esters, and β‐enaminones. Additionally, it has found application in other unsaturated systems su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…In the DeMayo-type [2 + 2] cycloaddition reaction, substrate triplet sensitization is a critical step. 36,40–42,44 Thus, our investigation emphasized elucidating how indole-based polycyclic organoPCs facilitate photosensitization that leads to the generation of the substrate triplet state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the DeMayo-type [2 + 2] cycloaddition reaction, substrate triplet sensitization is a critical step. 36,40–42,44 Thus, our investigation emphasized elucidating how indole-based polycyclic organoPCs facilitate photosensitization that leads to the generation of the substrate triplet state.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, our focus shifted toward understanding the photocatalytic process mechanism, particularly the origin of the superior reactivity of A and H. In the DeMayo-type [2 + 2] cycloaddition reaction, substrate triplet sensitization is a critical step. 36,40–42,44 Thus, our investigation emphasized elucidating how indole-based polycyclic organoPCs facilitate photosensitization that leads to the generation of the substrate triplet state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction starts with the direct irradiation of the mixture of keto - 1a and enol - 1a isomers with violet light (λ = 390–395 nm), the isomers absorb light energy and are immediately excited to its singlet excited state followed by ISC to its triplet excited state 3 1a *. The triple excited state 1a undergoes classical 6π electrocyclization, which produces transients 1,4-diradical A and B similar to the de Mayo reaction, and then trapped by tandem TEMPO-mediated direct HAT , or Cope-like elimination by losing TEMPOH to give the desired product 2a .…”
Section: Resultsmentioning
confidence: 99%
“…The photochemical reaction of β-diketones and double bonds under UV irradiation is referred to as the de Mayo reaction. [46] In 1962, Paul Jose de Mayo reported that the enol form of 1,3diketones could undergo a [2 + 2] cycloaddition reaction with alkenes under UV irradiation, yielding a cyclobutanol intermediate. This intermediate generates 1,5-diketones after ringopening.…”
Section: De Mayo Reactionsmentioning
confidence: 99%